I would advise teachers, who dream of great ideals, to start with these things, small perhaps, but that are none other than these ideals which we appreciate so much… On Juan Bardina’s unpublished paper (1909) - Ortega González, Eric; Garcia Farrero, Jordi; Margalef, Ferran Sánchez (Historia y Memoria de la Educación, 2020)
The present paper is an exercise in pedagogical archeology that rescues a relevant document for the history of Catalan pedagogy, and by extension, Chilean pedagogy, given the fact that Bardina resided in Chile for many years. We begin by presenting a paper, unpublished until now, that Juan Bardina presented in the Primary Teaching Conference of Barcelona (1909) and in which he summarizes what he considered to be the new education (the “stimulating pedagogy”, in his own words). We provide a brief biography of the author and some notes about his thought and pedagogical work, in order to contextualize, analyze and, where necessary, clarify the paper’s content. In it Bardina leaves traces of his filo-Americanism and his agreement with the postulates of Spencer about the philosophy of evolutionism. Finally, the reader will find the transcription of the paper, published for the first time.